The ladybeetle community (Coleoptera: Coccinellidae) in North East of Iran - Biranvand, A.; Nedvěd, Oldřich; Shakarami, J.; Fekrat, L.; Hamidi, E.; Volf, Martin; Hanley, G.A. (Akadémiai Kiadó, 2017)
Faunistical description of ladybird assemblages from the canopies of agricultural plants and orchard trees in northeastern Iran and determination of the indicator ladybird species that are representative of the region are the main goals of this survey. In total, 21 coccinellid species belonging to 16 genera were collected and identified. One previously recorded species (Bulaea lichatschovii (Hummel, 1827)) was not confirmed. Global distribution, list of known host plants, and prey species are provided for each species, along with latitude, longitude, altitude, and sampling methodology. Multivariate analysis of ladybird species assemblages composition and environmental variables (canonical correspondence analysis, CCA) showed that most ladybird species analysed did not express any strong preference for the environmental variables mainly because of intercorrelated characteristics of sampling localities. Seasonality was clear in three species; Adalia decempunctata was the earliest spring species while Coccinella septempunctata and Vibidia duodecimguttata were abundant at the end of season. Although analysis of food webs showed that twenty one collected ladybird species were directly connected to 30 host plant species, this does not represent specific food relationships because prey species in predatory ladybirds were not sampled and identified. Instead, this may probably be interpreted as choice of microhabitats.
Keywords: Aphids; Biogeography; Coccinellids; Distribution Fauna